Analysis of Event Marketing, Registration, and Ticketing Digitalization - Yohanes Priadi Wibisono; Clara Hetty Primasari; Saverius Rischo Setyo Kurniawan (Maranatha University Press, 2020)
Almost all parts in an organization both commercial and non-commercial must have held an event. No exception in the education, especially at the University. The number of events carried out on campus is a phenomenon that makes students who are members of organizations learn to organize it so that it can run well. Organizing events is not easy and requires a lot of energy, time and costs starting from marketing, registering, ticketing, participant validation, and distribution of certificates. The aim of this research is to analyze the ineffectiveness and inefficiencies that occur in running an event. Analysis and observations were made based on the processes that took place in the holding of events held by students at Universitas Atma Jaya Yogyakarta. The process will be simplified by utilizing digital media so that the process of making an event becomes more effective and efficient. This research resulted in a BPR (Business Re-engineering Process) in which the marketing, registration, and ticketing processes that were originally done manually were, converted to digital with a web-based system. It is expected that from this BPR, researchers can develop an application to digitalize marketing, online event registration, ticketing, and event validation using QR Code. Keywords— event; marketing; promotion; QR code; registration